The constitutional principle of contradictory and defense in administrative disciplinary process (Revista Digital de Direito Administrativo, 2014)
This article is a study on the incidence of procedural constitutional principles - due process, contradictory and full defense - arguing that these are not limited to judicial proceedings and that they should be extended to the sphere of administrative enforcement by the constitution, in order to verify whether those Constitutional principles are observed by the public in the conduct of administrative disciplinary proceedings.